Investigating characteristics and possible origins of off‐odor substances in various yeast extract products. Issue 5 (12th March 2020) - Zheng, Yingying; Yang, Ping; Chen, Erbao; Song, Huanlu; Li, Pei; Li, Ku; Xiong, Jian
Abstract: Yeast extract (YE) is rich in amino acids, nucleotides, peptides, and other flavor substances, and is a natural nutrient, umami, and flavor enhancer. However, certain YE samples impart a yeasty flavor that affects the quality parameters of YE. We compared solid‐phase microextraction (SPME), solvent‐assisted evaporation (SAFE), dynamic headspace sample preparation (DHS), stir bar sorptive extraction (SBSE), and other pretreatment methods for the extraction of volatiles substances in YE. SPME was selected as a suitable extraction method, and aroma extract dilution analysis (AEDA) was combined with gas chromatography‐olfactometry‐mass spectrometry (GC‐O‐MS) for identification of key odor‐active compounds in 23 YE samples. The yeast off‐odor substances were screened from these compounds. Principal component analysis (PCA) was used to investigate the relationship between strains and the processing of YE products and their yeasty flavor. Practical applications: YE is prepared primarily from baker's yeast or waste beer yeast by autolysis or enzymatic hydrolysis, and is rich in nucleotides, peptides, amino acids, and other flavor compounds. It is used globally as a common umami and flavor enhancer. However, consumers have observed that YE imparts a certain yeasty flavor that influences the overall flavor negatively. Hence, the yeasty flavor‐imparting substances from 23 YE samples were investigated in this study, and the observations (including strains, processing techniques, etc.) were integrated to explain the relationship between the yeasty flavor of the YE products with strain (different yeast strain for production) or processing of YE products (enzymes used, enzymatic hydrolysis conditions, composition of products, concentration conditions of YE, etc.), or storage conditions (temperature, humidity, duration, package, etc.), providing a scientific basis for removal/lowering or masking of yeasty flavor and the improvement of flavor quality of YE products. Abstract : Odorants in 23 YE samples were identified and quantitatively analyzed. Of them, yeasty off‐odor compounds were screened out by aroma model. Differences in strains and processing of YE may be the possible causes of yeasty note.